Effect of milling process for rice husk ash on mechanical strength of blended Portland cement mortars - Da Silva, Everton Jose; Marques, Maria L.; Vasconcelos, Antonio R. B. [UNESP]; Akasaki, Jorge L. [UNESP]; Tashima, Mauro M.; Pereira, Adriana M. [UNESP] (Trans Tech Publications, 2014)
Nowadays, the reuse of waste products in the construction process is a priority research area. Several industrial and agricultural waste products have been investigated, such as fly ash, sugar cane bagasse ash and rice husk ash. This paper analyses a very important topic under intense discussion in the scientific community: the Rice Husk Ash (RHA) grinding process. This paper investigates a low carbon RHA with high pozzolanic reactivity produced under uncontrolled burning conditions. The compressive strength of mortar specimens prepared using both ground and natural RHA were tested for 3-56 days and the capillary absorption was measured for mortars cured during 28 days. Very promising and interesting results were obtained using natural rice husk ash in the production of blended mortars. © (2014) Trans Tech Publications, Switzerland.
Keywords: Compressive strength; Grinding process; Mortars; Rice husk ash